Geochemical characteristics of late Quaternary sediments from the southern Aegean Sea (Eastern Mediterranean) - SIOULAS, A.; ANAGNOSTOU, CH.; KARAGEORGIS, A.P.; GARBE-SCHONBERG, C.D. (Mediterranean Marine Science, 2000)
Ten cores from the southern Aegean Sea have been logged for their lithological composition and seventy-three sub-samples were analysed for the determination of major and trace elements concentrations. Four lithological units were identified, namely, mud, volcanic, turbidite and sapropel. On the basis of the “Z-2” Minoan ash layer radiocarbon age sedimentation rates for the southern Aegean Sea were estimated at 3.26 to 4.15 cm kyr -1. Simple correlation analysis revealed three groups of elements associated with: (1) biogenic carbonates; (2) terrigenous alumino-silicates and (3) sapropelic layers. R-mode factor analysis applied on the carbonate-free corrected data-set defined four significant factors: (1) the “detrital alumino-silicate factor” represented by Si, Al, Na, K, Rb, Zr, Pb and inversely related to Ca, Mg, and Sr; (2) a “hydrothermal factor” loaded with Cr, Ni, Co, Cu, Fe; (3) the “volcanic ash factor” with high loadings for Ti, Al, Fe, Na and (4) a “sapropel factor” represented by Ba, Mo, and Zn. High factor scores for the “hydrothermal factor” were observed in sediment samples proximal to Nisyros Isl., suggesting a potential hydrothermal influence. Red-brown oxides and crusts dredged from this area support further this possibility. The use of factor analysis enabled for a better understanding of the chemical elements associations that remained obscured by correlation analysis.